On the rumba river [videorecording (DVD)] - Sarasin, Jacques; Wendo Kolosoy, 1925-2008 (First Run Features, 2008)
Journey on the Congo River and through the life of Antoine 'Wendo' Kolosoy, from his beginnings as an orphan to his rise as the superstar of Congolese Rumba, to having his music banned by the dictator Mobuto, and many years later to his comeback, as he searches for old bandmates and plays his joyous music.